Language expressions of politeness in japanese (Journal of Oriental Studies, 2016)
This article defines the termin «politeness», from the grammatical point of view. Traditionally used to describe variety of means of linguistic expression and social relations between the speakers. The several ways of expressing politeness in Japanese were researched.
Keywords: politeness; politeness category; ways of expressing politeness